Prelude. "You Need a Big God". Fascinating Interactions Between Music and Religion Prelude. - Natalie Fritz (Journal for Religion, Film and Media, 2020)
The Praelude "You Need a Big God" tries to approach the thematic field of religion and popular music using a variety of music video clips to highlight the manifold interactions and interrelations between popular music and religion. Aspects like the production, distribution and consumption of music that in one or another way deals with religion, religiosity or spirituality are highly significant to understand how both cultural symbol systems affect and are affected by the other.